2016
DOI: 10.1152/jn.00008.2016
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal distribution of location and object effects in the electromyographic activity of upper extremity muscles during reach-to-grasp

Abstract: Rouse AG, Schieber MH. Spatiotemporal distribution of location and object effects in the electromyographic activity of upper extremity muscles during reach-to-grasp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Although reaching and grasping traditionally have been considered to be mediated through independent channels ( Jeannerod, 1984 ), considerable evidence suggests that under appropriate conditions, variation in reaching affects grasping and vice versa ( Wallace and Weeks, 1988 ; Paulignan et al, 1991 ; Hoff and Arbib, 1993 ; Haggard and Wing, 1998 ; Connolly and Goodale, 1999 ). Our previous studies of the present RGM movements have shown that location-related variance predominates early and object-related variance later, not only in the activity of individual M1 neurons ( Rouse and Schieber, 2016a ) but also in the EMG activity of individual muscles ( Rouse and Schieber, 2016b ) and in the kinematics of individual joints ( Rouse and Schieber, 2015 ). Our findings here that a similar population of neurons in the motor cortex is related both to reach location and to the object grasped and manipulated—but with progressively shifting neural dimen-sions of activity—may provide a framework to better understand these observations.…”
Section: Discussionmentioning
confidence: 67%
“…Although reaching and grasping traditionally have been considered to be mediated through independent channels ( Jeannerod, 1984 ), considerable evidence suggests that under appropriate conditions, variation in reaching affects grasping and vice versa ( Wallace and Weeks, 1988 ; Paulignan et al, 1991 ; Hoff and Arbib, 1993 ; Haggard and Wing, 1998 ; Connolly and Goodale, 1999 ). Our previous studies of the present RGM movements have shown that location-related variance predominates early and object-related variance later, not only in the activity of individual M1 neurons ( Rouse and Schieber, 2016a ) but also in the EMG activity of individual muscles ( Rouse and Schieber, 2016b ) and in the kinematics of individual joints ( Rouse and Schieber, 2015 ). Our findings here that a similar population of neurons in the motor cortex is related both to reach location and to the object grasped and manipulated—but with progressively shifting neural dimen-sions of activity—may provide a framework to better understand these observations.…”
Section: Discussionmentioning
confidence: 67%
“…For further selection, we calculated from the spike shapes of each neuron the signal-to-noise ratio (SNR), defined as the amplitude, i.e., the mean of the trough-to-peak voltage, divided by twice the standard deviation of the entire signal (Hatsopoulos et al, 2004 ). For this study we selected only single neurons with SNR values >2.5 to guarantee good sorting quality (see also Rouse and Schieber, 2016 ). The distributions of the SNR values of all neurons are shown in Figure 1E .…”
Section: Methodsmentioning
confidence: 99%
“…Because we chose to study relatively naturalistic movements, the reach, grasp, and manipulation components were not performed separately, but rather in a continuous fluid motion during the movement epoch of the task sequence (Figure 2B). In previous studies of a version of this task without separate instruction or delay epochs, we have shown that joint kinematics, EMG activity, and neuron activity in the primary motor cortex, all vary throughout the movement epoch in relation to both reach location and object, with location predominating early in the movement epoch and object predominating later (Rouse and Schieber, 2015, 2016b, a). Our task thus did not dissociate the reach, the hand shape used to grasp the object, and the manipulation performed on the object.…”
Section: Resultsmentioning
confidence: 88%
“…The monkey then reached to, grasped, and manipulated the remembered target object: turning a sphere, pushing a button, pulling a coaxial cylinder (coax), or pulling a perpendicular cylinder (perp). The reach, grasp, manipulate sequence was performed as a single, uninterrupted, fluid movement of the entire upper extremity (Rouse and Schieber, 2015, 2016b, a). Once the instructed object had been manipulated, a ring of green LEDs around the object illuminated (indicating successful manipulation of the object) and the ring of blue LEDs for that object also illuminated (indicating correct object).…”
Section: Methodsmentioning
confidence: 99%